Annual Plan 1971-72 (Statistical Data) Government of Andhra Pradesh - Planning Commission (Planning Commission, 1971)
According to the formula of allocation of funds for the three regions of Coastal Andhra, Rayalaseema and Telangana approved by the Government of India for 1971-72, the allocation of resources is on the basis of 90% based population, with the balance of 10% for backwardness with distribution pro-rata on population within the backward areas. The Plan for 1971-72 has accordingly been prepared.
Government of Andhra Pradesh, Planning and Co-operation Department
Government of Andhra Pradesh, Planning and Co-operation Department